DSE (AGING SEMANTIC DIFFERENTIAL) CONSTRUCTION AND ASSESSMENT IN DIFFERENT COHORTS - Villar Posada, Feliciano (Anales de Psicología / Annals of Psychology)
This paper is aimed at examining both the attitudes towards the aging process and the age-related differences in such attitudes. The data were collected using an 18 items scale -based on the semantic differential technique-developed from a pilot study with 82 subjects. Once the sample was piloted, 166 subjects belonging to six different cohorts aswered the items.. Our results seem to point out that our scale presented good psychometric properties. The mean score in the scale located attitude towards aging near the neutral point. With respect to the relationship between attitude and age, the older cohort held the most positive atttitude, whereas people between 40 and 59 years old held the most negative one. These findings are discussed and new research is proposed.